PENGEMBANGAN MEDIA PEMBELAJARAN TARI BERWAWASAN PEDULILINGKUNGAN DI SEKOLAH DASAR - Riri Wulandari; Zufriady; Neni Hermita (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
At present, there are still some teachers who when teaching use leatoring and demonstration methods. It influences less effective teaching and learning and takes a lot of timeand energy to explain process by process  when teaching in class. To avoid this, we need the right media that can describe each process from preparation to completion without having totake a long time and can  be reused and attract students' interest  inlearning so that students donot feel bored when studying. Hence, a teacher is required to be able to create a learning media. By using learning media, teachers will be easier to convey material so that learningmedia can be used as media that combines sound with images so that it will attract more attention during the learning process. In addition, learning media also has advantages, one of them is that it can be seen repeatedly if we need it. This article is focused on the developmentstudy of dance learning media based on environmental care. Based on the   of the study, the average total score of media validity showed 88% in the ‘very valid’ category and the average total score of product try-out showed 94.02% in the ‘very good’ category. Thus, developed dance learning media could be said feasible and used by teacher and students in Art, Culture, and Craft learning subject in elementary school.